Kedudukan Harta Bawaan dan Harta Bersama setelah Perceraian: Studi Perjanjian Pranikah - Abdul Muthalib Rimi (CV. Social Politic Genius (SIGn), 2022)
This study aims to examine and analyze the position of the premarital property and joint property in the prenuptial agreement and the legal consequences after the divorce. This normative legal study uses a statute and comparative approaches with a literature study technique. The results show that premarital and joint property have different marital positions. Premarital property refers to property owned individually by the husband or wife before marriage. In contrast, joint property refers to property acquired during the marriage and jointly owned by husband and wife. At the time of the divorce, the joint property becomes the object of division, whereas the premarital property remains excluded from division unless regulated in the prenuptial agreement. If the divorce occurs without a prenuptial agreement, the division of joint property must be executed after a court decision is obtained, which has become final and binding. On the other hand, although the prenuptial agreement serves as a legal means of proof, the judge may ignore it for several reasons. That judge’s consideration can provide legal consequences for the prenuptial agreement in a divorce decision. Therefore, it is recommended that prospective spouses, notaries, and judges, need to understand the differences between premarital and joint property and the legal consequences related to divorce. Prospective spouses are advised to make clear and detailed prenuptial agreements regarding property division in the event of a divorce, thereby reducing potential conflicts and disputes. The notary should assist prospective spouses in drafting fair agreements under applicable laws. Judges, in turn, need to objectively consider prenuptial agreements and ensure that decisions align with both parties’ interests and the principles of justice.